2012
DOI: 10.1039/c2sm26328a
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pattern formation based on the coffee-ring effect for organic–inorganic hybrid films prepared by dip-coating: effects of temperature during deposition

Abstract: We prepared silica-poly(vinylpyrrolidone) (PVP) hybrid films via a temperature-controlled dip-coating process and investigated the influence of the coating temperature (i.e., the temperature of substrates, solutions and atmosphere) on the spontaneous pattern formation based on the ''coffee-ring effect''. Micron-scale stripe patterns were spontaneously formed on the surface of the films at high coating temperatures over 40 C during dip-coating. The stripe patterns were arranged perpendicular to the withdrawal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 34 publications
(52 reference statements)
1
16
0
Order By: Relevance
“…During such low-speed dip coating, the evaporation-driven deposition locally progresses at the edge of the meniscus, resulting in the film formation on the substrates (Figure ). ,, In the present case, the evaporation-driven deposition of WO 3 precursors was observed for all coating solutions as shown in Table . Table also shows the deposition area of the WO 3 precursors on the substrates, and the optical micrographs of the precursors are shown in Figure and Figure S1 of the Supporting Information.…”
Section: Resultssupporting
confidence: 54%
“…During such low-speed dip coating, the evaporation-driven deposition locally progresses at the edge of the meniscus, resulting in the film formation on the substrates (Figure ). ,, In the present case, the evaporation-driven deposition of WO 3 precursors was observed for all coating solutions as shown in Table . Table also shows the deposition area of the WO 3 precursors on the substrates, and the optical micrographs of the precursors are shown in Figure and Figure S1 of the Supporting Information.…”
Section: Resultssupporting
confidence: 54%
“…Beyond flow stress or flow rate, factors such as particle volume fraction, fluid viscosity, particle interaction potentials, and size polydispersity are responsible for dictating the resulting order in the system. Flow can be generated by a number of means including simple shear, evaporation, surface‐tension gradients (Marangoni flows), capillary force, and pressure/temperature differences . Shear‐induced assembly is commonly used, and the shear‐induced assembly of hybrid nanocomposites has been well established .…”
Section: Directed Assemblymentioning
confidence: 99%
“…Uchiyama et al reported preparation of regular stripe patterns of organic-inorganic hybrid films through mechanical dip-coating (Figure 3) [43]. A temperature-controlled dip-coating from a solution of tetramethyl orthosilicate and poly(vinylpyrrolidone) results in the spontaneous formation of a striped pattern.…”
Section: Nanofabrication Based On Mechanical Processesmentioning
confidence: 99%